2007
DOI: 10.1080/00131910600796827
|View full text |Cite
|
Sign up to set email alerts
|

Chinese American post‐secondary achievement and attainment: a cultural and structural analysis

Abstract: In this article, the authors compare Chinese American post-secondary educational attainment with that of White Americans and, in identifying those factors that most strongly account for success, argue that commonalities exist among social structural factors, while distinct differences are evident among cultural capital factors. The article rejects the notion of minority assimilation as the source of success and suggests that Chinese and White cultures, in promoting education, are harmonistic but different.Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
4
28
0
Order By: Relevance
“…Asian adolescents reported the highest academic achievement among all ethnic groups. Such findings may reflect the academically focused Asian culture (Pearce & Lin, 2007). Furthermore, children of college-educated parents also tended to have higher academic achievement than children of parents holding only a high school diploma.…”
Section: Discussionmentioning
confidence: 92%
“…Asian adolescents reported the highest academic achievement among all ethnic groups. Such findings may reflect the academically focused Asian culture (Pearce & Lin, 2007). Furthermore, children of college-educated parents also tended to have higher academic achievement than children of parents holding only a high school diploma.…”
Section: Discussionmentioning
confidence: 92%
“…In the meantime, for those who use the datasets that are available despite their limitations, the limits must be identified and discussed so that it is clear what is and what is not actually evidenced in the study. More work should be conducted to find exemplars of ways to operationalize the nuances of cultural capital (see, for example, Pearce and Lin, 2007).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The findings indicated that the cultural capital was related to academic achievement. But the cultural capital of Chinese Americans was evidenced to be rooted in their culture as a nondominant form of cultural capital while White American students appeared to possess cultural capital rewarded by schools, dominant forms of cultural capital (also see Pearce and Lin, 2007).…”
Section: Nondominant or Otherized Cultural Capitalmentioning
confidence: 96%
“…Several explanations have been proposed to account for the high achievement among Chinese Americans. A study by Pearce and Lin () indicated that social structure (i.e., gender, family income, urbanicity, and family composition) and cultural capital (i.e., parents’ education, educational expectation, parental involvement, and parenting style) might be two main contributors to Chinese Americans’ high achievement. Compared to their White American counterparts, parent educational attainment and parental expectations have more impact on Chinese‐American students (Pearce & Lin, ).…”
Section: A Profile For Chinese‐american Students and Familiesmentioning
confidence: 99%